Knowledge of Families of Patients with Diarrhea Prevention in The in-Treatment Room of Academis Hospital Makassar - Sudarmin, Ria Rezeki; Kadir, Erni; Tarukallo, Yohanis; Tobondo, Yuyun Alfasius; Tahir G, Muhammad; Qasim, Muhammad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Based on the results of research related to diarrheal diseases in various regions in Indonesia, there are several interrelated factors, namely inadequate supply of clean water, water polluted by feces, lack of sanitation facilities, unhygienic disposal of feces, poor personal and environmental hygiene, and improper processing and storage of food. Many factors can directly or indirectly be a driving factor for the occurrence of diarrhea, consisting of host agent, environmental and behavioral factors. The purpose of this study was to determine the relationship between the knowledge of the patient's family and the prevention of diarrheal diseases at the Makassar Akademis Hospital. This type of research is descriptive with the research design used is the Cross-Sectional method, namely the type of research that emphasizes the time of measurement / observation of independent and dependent variable data only once. Place This research was conducted in the inpatient room of the Makassar Akademis Hospital. According to the results of data analysis using the chi-square statistical test, a value of p = 0.000 (p <0.05) was obtained, this means that there is an environmental relationship with the incidence of diarrhea in toddlers in the child care room at the Makassar Akademis Hospital. The conclusion is that there is a relationship between environmental, socio-economic conditions, and mother's knowledge with the incidence of diarrhea in the child care room at the Makassar Akademis Hospital.